Evidence-based anatomical review areas derived from systematic analysis of cases from a radiological departmental discrepancy meeting. Issue 10 (October 2017) - Chin, S.C.; Weir-McCall, J.R.; Yeap, P.M.; White, R.D.; Budak, M.J.; Duncan, G.; Oliver, T.B.; Zealley, I.A.
Abstract : Aim: To produce short checklists of specific anatomical review sites for different regions of the body based on the frequency of radiological errors reviewed at radiology discrepancy meetings, thereby creating "evidence-based" review areas for radiology reporting. Materials and methods: A single centre discrepancy database was retrospectively reviewed from a 5-year period. All errors were classified by type, modality, body system, and specific anatomical location. Errors were assigned to one of four body regions: chest, abdominopelvic, central nervous system (CNS), and musculoskeletal (MSK). Frequencies of errors in anatomical locations were then analysed. Results: There were 561 errors in 477 examinations; 290 (46%) errors occurred in the abdomen/pelvis, 99 (15.7%) in the chest, 117 (18.5%) in the CNS, and 125 (19.9%) in the MSK system. In each body system, the five most common location were chest: lung bases on computed tomography (CT), apices on radiography, pulmonary vasculature, bones, and mediastinum; abdominopelvic: vasculature, colon, kidneys, liver, and pancreas; CNS: intracranial vasculature, peripheral cerebral grey matter, bone, parafalcine, and the frontotemporal lobes surrounding the Sylvian fissure; and MSK: calvarium, sacrum, pelvis, chest, and spine. Conclusion: The five listed locations accounted for >50% of all perceptual errors suggesting an avenue for focused review at the end of reporting. Highlights: Observational errors were the most common, followed by communicative errors and technical errors. Of the observational errors, false negative errors were made most frequently. Over 50% of discrepancies analysed were located in five or fewer locations.